Development of the first-mention bias() - HARTSHORNE, JOSHUA K. (J Child Lang, 2014)
In many contexts, pronouns are interpreted as referring to the character mentioned first in the previous sentence, an effect called the ‘first-mention bias’. While adults can rapidly use the first-mention bias to guide pronoun interpretation, it is unclear when this bias emerges during development. Curiously, experiments with children between two and three years old show successful use of order of mention, while experiments with older children (four to five years old) do not. While this could suggest U-shaped development, it could also reflect differences in the methodologies employed. We show that children can indeed use first-mention information, but do so too slowly to have been detected in previous work reporting null results. Comparison across the present and previously published studies suggests that the speed at which children deploy first-mention information increases greatly during the preschool years.